2014
DOI: 10.1016/j.jcot.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Primary repair of capsuloligamentous structures of trapeziometacarpal joint: A preliminary study

Abstract: a b s t r a c tBackground: Isolated trapezio-metacarpal joint dislocation is uncommon and challenging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
3
Order By: Relevance
“…Fotiadis et al , Okita et al and Ansari et al used suture anchors to perform the ligament reconstruction, with success 5 14 15. All three authors reported good functional outcome and radiographs showing normal joint anatomy at minimum 1 year’s follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fotiadis et al , Okita et al and Ansari et al used suture anchors to perform the ligament reconstruction, with success 5 14 15. All three authors reported good functional outcome and radiographs showing normal joint anatomy at minimum 1 year’s follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous case reports and case series suggested an attempt at a closed reduction of this joint as the first line of management 4–16. If the joint was stable post-reduction, the joint could be immobilised in a thumb spica cast or splint for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Escolhas de tratamento variam desde a redução fechada e imobilização com gesso e redução fechada e fixação com fios Kirschner até a redução aberta com reparo capsular e reconstrução do ligamento. [1][2][3][4][5][6][7][8][9][10] A primeira articulação carpometacarpal é uma articulação em forma de sela, que é responsável pela mobilidade extraordinária e função importante do polegar. 1 Se essa luxação não é diagnosticada ou tratada corretamente, pode resultar em instabilidade mecânica crônica, deficiência na mão, e mudanças articulares degenerativas.…”
Section: Introductionunclassified
“…1 Se essa luxação não é diagnosticada ou tratada corretamente, pode resultar em instabilidade mecânica crônica, deficiência na mão, e mudanças articulares degenerativas. 4,9 Os autores apresentam dois casos de luxação traumática isolada da articulação trapézio-metacárpica. Um desses casos foi tratado com redução fechada e imobilização com gesso, e o outro foi tratado com redução fechada, fixação com fios Kirschner, e imobilização com gesso.…”
Section: Introductionunclassified
“…However, Strauch et al [6] found that the dorsoradial ligament was the primary restraint to dorsal dislocation in their cadaveric studies. Recently, some authors have introduced repair of the dorsal ligament using suture anchors based on the findings [7] [8] [9] [10]. The purpose of the study was to present our surgical procedures and evaluate the clinical outcome after repair of the dorsal capsulo-ligamentous complex using suture anchors.…”
Section: Introductionmentioning
confidence: 99%